2009
DOI: 10.2466/pms.108.2.411-421
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Stages of Change in Turkish University Students by Sex, Residence, and Department

Abstract: To examine the exercise behavior of 953 Turkish university students (496 men, 457 women) by sex, residence, and department of study, a stratified sampling method, based on the total number of students in each department, was used to select participants. The mean age of the participants was 21.3 yr. (SD = 1.9). For completed Physical Activity Stages of Change Questionnaire and the International Physical Activity Questionnaire, descriptive statistics and chi-squared tests indicated that most students were at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 23 publications
3
18
0
2
Order By: Relevance
“…While the General Health Status Questionnaire was used to identify health status, the Exercise Stage of Change Questionnaire-ESOC (18) was employed to determine the physical activity level of the subjects. The validity and reliability of the Turkish version of the ESOC were tested by Cengiz et al (19). The experimental protocol was approved by the (Middle East Technical University Graduate School of Natural and Applied Sciences No:78-1597) local ethics committee.…”
Section: Subjectsmentioning
confidence: 99%
“…While the General Health Status Questionnaire was used to identify health status, the Exercise Stage of Change Questionnaire-ESOC (18) was employed to determine the physical activity level of the subjects. The validity and reliability of the Turkish version of the ESOC were tested by Cengiz et al (19). The experimental protocol was approved by the (Middle East Technical University Graduate School of Natural and Applied Sciences No:78-1597) local ethics committee.…”
Section: Subjectsmentioning
confidence: 99%
“…In addition, most of the above mentioned previous studies in Turkish context conducted in school aged population (Daskapan et al, 2006;Savci et al, 2006;Cengiz et al, 2009;İnce & Ebem, 2009;Koca et al, 2009;Kin-İşler et al, 2009;Karaca et al , 2009). This causes a serious limitation in the generalization of the findings to older adult population.…”
mentioning
confidence: 99%
“…Sex differences in PA level presented in a number of studies previously (WHO, 2010;Trost et al, 2002;Cengiz et al, 2009;Ince & Ebem 2009). These studies indicated a higher PA level in men as compared to women population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also suggest that university students should participate more in physical activities in university years. [11][12][13][14][15][16]. Okazaki et al [17] report that 46.7 of male university students and 61.3 female university students fail to satisfy the need for daily physical activity suggested by the World Health Organization [2].…”
mentioning
confidence: 99%